Innovate the future : a radical new approach to IT innovation - Croslin, David (Prentice Hall, 2010)
When it comes to entering, creating, or dominating markets, disruptive innovation is the most powerful tool you have. Unfortunately, most companies find disruptive innovation difficult to achieve and virtually impossible to replicate. In Innovate the Future, renowned technology innovator David Croslin helps you solve this problem once and for all. Croslin introduces a proven process for consistently creating inventions, technologies, and methods that are truly transformative.